Is poly(propylene carbonate) biodegradable? Synthesis of poly(propylene carbonate)-containing star and block copolymers and comprehensive investigation on their biodegradation - Yang, Hee Seong; Cho, Woo Yeon; Seo, Yeong Hyun; Chae, Ju Hyung; Lee, Pyung Cheon; Lee, Bun Yeoul; Lee, In Hwan (Journal of Polymer Science, 2024)
Storing CO2 and converting it into valuable substances are crucial for addressing climate change. While poly(propylene carbonate) (PPC), formed through the copolymerization of CO2 and propylene oxide, holds promise in commercial applications, practical limitations arise due to inherent property constraints. Additionally, the lack of systematic research on PPC biodegradation complicates its post-use disposal. In this study, we synthesized various polymers, including PPC homopolymers, PPC/castor oil star copolymers, and PPC/poly(l-lactic acid) multiblock copolymers (PPC-mb-PLLAs), not only to mitigate the brittle properties of PPC but also to systematically explore their biodegradability. Both natural soil and industrial composting conditions were employed to assess the biodegradation of the polymers. Furthermore, metagenomic analysis identified the microorganisms responsible for polymer degradation, offering valuable insights into the mechanism of the biodegradation process.
Keywords: Block co polymers; Castor oil; Copolymerisation; Poly(propylene carbonate); Polypropylene carbonate; Property; Propylene carbonate; Propylene oxide; Star copolymers; biodegradation; block copolymer; carbon dioxide; castor oil; poly(propylene carbonate)